Relationship dynamics and divorcing mothers' adjustment: Moderating role of marital violence, negative life events, and social support. (November 2019) - Hardesty, Jennifer L.; Ogolsky, Brian G.; Raffaelli, Marcela; Whittaker, Angela
Longitudinal associations between postseparation relationship stressors (coparenting conflict and harassment) and health outcomes (depressive, posttraumatic stress disorder [PTSD], and physical health symptoms) as moderated by contextual factors (i.e., marital intimate partner violence [IPV], negative life events, and social support) were examined in a sample of divorcing mothers. Respondents were 135 mothers recruited within 4 months of a divorce filing who participated in five interviews at 3-month intervals over a 1-year period. Multilevel modeling procedures used to account for the repeated assessments over time revealed direct associations between postseparation stressors and health outcomes differing based on IPV and negative life events. For example, coparenting conflict after separation was associated with higher levels of depressive, PTSD, and physical health symptoms among mothers who experienced no violence, whereas the opposite pattern was observed among mothers whose marriages were characterized by coercive controlling violence. Negative life events magnified that negative impact of coparenting conflict on mental and physical health. Contrary to expectation, social support did not diminish the negative health effects of postseparation stressors. Findings support the value of examining how distinct postseparation factors are associated with divorcing mothers' health within the broader context against which the divorce process plays out.